Investigation of In Vitro Cytotoxic and Genotoxic Properties of New Dioxybiphenyl-bridged Spiro Cyclotrifosphazene with Dihydroxycoumarin Groups Synthesized by the Click Method - Keskin, Tuba; Savasci, Zeynep; Seker, Ferhan Sultan; Cetiner, Rumeysa; Biryan, Fatih; Koran, Kenan; Sandal, Suleyman (Wiley, 2025)
[Abstract Not Available]
Keywords: Dyspirocyclotriphosphazene; A2780; MCF-7; MTT Assay; Comet Assay